Efektivitas Bahan Ajar Larutan Buffer Terintegrasi Nilai-Nilai Islam Terhadap Hasil Belajar Siswa SMA/MA - Urwatil Wutsqo Amry (FKIP University of Mataram, 2026)
This study examines the effectiveness of Islamic values–integrated buffer solution teaching materials on students’ learning outcomes. A quantitative approach with a quasi-experimental post-test only control group design was employed. The sampling technique used in this study was cluster random sampling technieque, there were two schools elected as samples; MA Unwanul Falah Paok Lombok (Suralaga) and MA Al-Ijtihad Danger, in which each school consisted of experiment and control group.. The experimental group was taught using Islamic values–integrated buffer solution teaching materials, while the control group used conventional teaching materials. Learning outcome data were collected through a post-test and analyzed using an independent samples t-test and a two-way ANOVA. The results indicate that the Islamic values–integrated buffer solution teaching materials have a significant effect on students’ learning outcomes. In addition, an interaction effect between the type of teaching materials and school context was identified. These findings suggest that the effectiveness of chemistry teaching materials is influenced by the alignment between instructional design and the learning environment